Экология сокола дербника (Falco columbarius L.) в Белорусском Поозерье - Дорофеев, A.M.; Ивановский, В.В. (Вестник зоологии, 1980)
The paper deals with the data obtained in 1962-1979 on the Falco columbarius nesting, nutrition and number in the Byelorussian Poozerie. Recommendations on this rare species protection are given.